Sexual And Reproductive Health Needs, Experiences, Access To Services, And Interventions Among The Rohingya And The Afghan Refugee Women Of Reproductive Age In Asia: A Mixed Methods Systematic Review Protocol - Muhammad Anwar Hossain; Angela Dawson (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2021)
Background: A humanitarian crisis disrupts the existing health care system limiting access to sexual reproductive health (SRH) services. The Asia and the Pacific region is home to 9.2 million refugees as of September 2020, most originating from Afghanistan and Myanmar. Afghan and Rohingya refugees have long been deprived of formal SRH education and face decades of discrimination in SRH services that can affect health outcomes. Purpose: This review examines the SRH status of Afghan and Rohingya refugee women of reproductive age in Asia and their needs and experiences in accessing these services and commodities. Methods: This protocol will follow the PRISMA checklist and standards for quality assessment of systematic reviews. The search strategy will be sought out all relevant peer-reviewed literature from five online bibliographic databases—SCOPUS, EMBASE (Ovid), MEDLINE (Ovid), CINAHL, and PROQUEST— using search terms related to the research questions. The review will include qualitative, quantitative, and mixed-method studies to understand the status of SRH of Rohingya and Afghan refugees across Asia. Content analysis will undertake following the Minimum Initial Service Package (MISP) objectives. The review will use the mixed methods appraisal tool (MMAT) to assess the quality of individual studies. However, no studies will be excluded based on this assessment. Result: The findings of this review will provide insight into the needs, status, and experiences of SRH of the Afghan and Rohingya refugee women of reproductive age in Asia and could contribute to health service planning to deliver evidence-based interventions and policies to improve SRH outcomes in humanitarian settings across Asia. Systematic review registration: The review was registered in the PROSPERO database with ID CRD42021253975.